Evaluation of Solar Chimney Power Plant in Semi-Arid Region of Nigeria - Ngala, G. M.; Oumarou, M. B.; Mohammad, A. B.; Shuwa, M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2015)
Solar chimney power plant (SCPP) is a renewable energy facility that converts the potential energy in the Sun intokinetic energy and subsequently into electrical energy. The problem of global warming and electricitygeneration/distribution in Nigeria cannot be over emphasized; however with the vast land in the semi arid region andthe potentials of the above technology, high prospects exist for solar chimney as it is a decentralized form of powergeneration. The aim of this paper was to theoretically evaluate the performance of the solar chimney power plant insemi-arid region of Nigeria, and estimate the amount of electrical energy that can possibly be generated. Amathematical model was used to estimate the amount of power generated, and determine the relationship betweenvarious meteorological and physical factors to the power produced. A solar chimney power plant with collectordiameter of 700 m and chimney height of 700 m can produce up to 3000 MW of electricity